“Hoje, Como Sempre, Um Dia De Luta”: : Resistência Indígena E Práxis Educativa (PERcursos Linguísticos, 2023)
This issue proposes a reflection about the way in which indigenous people have placed themselves as historical subjects opposite people who silence and objectify their lives. The data was generated at the event “Direitos indígenas e a atual conjuntura política brasileira”, promoted by the Associação dos Estudantes Indígenas da Universidade Federal de Santa Catarina (AEIUFSC), organized immediately later the confirmation of Jair Bolsonaro as Brazilian President. The speeches of the elected candidate represent a threat to indigenous peoples, especially in relation to the right to demarcate their lands, so indigenous students at the Federal University of Santa Catarina felt the emerging need to problematize the situations in which they could be exposed. The land is a sacred place and where linguistic-cultural practices are conducted for these people. Therefore, the discussions present here are urgently necessary.